Exploring ecodynamics of coastal foragers using integrated faunal records from Čḯxwicən village (Strait of Juan de Fuca, Washington, U.S.A.). (February 2019) - Butler, Virginia L.; Campbell, Sarah K.; Bovy, Kristine M.; Etnier, Michael A.
Abstract: Extensive 2004 excavation of Čḯx w icən (pronounced ch-WHEET-son ), traditional home of the Lower Elwha Klallam Tribe in northwest Washington State, U.S.A., documented human occupation spanning the last 2700 years with fine geo-stratigraphic control and 102 radiocarbon samples. Remains of multiple plankhouses were documented. Occupation spans large-magnitude earthquakes, periods of climate change, and change in nearshore habitat. Our project began in 2012 as a case study to explore the value of human ecodynamics in explaining change and stability in human-animal relationships on the Northwest Coast through analysis of faunal and geo-archaeological records. Field sampling was explicitly designed to allow for integration of all faunal classes (birds, fish, mammals, and invertebrates), thus facilitating our ability to track how different taxa were affected by external factors and cultural processes. With over one million specimens, the faunal assemblage represents one of the largest on the North Pacific Coast. Invertebrate records reveal striking changes in intertidal habitat that are linked to the formation of the sheltered harbor and catastrophic events such as tsunamis. Analysis suggests a high level of consistency in the structure of resource use (evenness and richness) across 2150 years of occupation, despite increase in intensity of human use and a shift to plankhouse occupation. Trends in fish and invertebrate representation do not correspond to changing ocean conditions, while changes in abundance of herring, salmon, burrowing bivalves and urchins are consistent with impacts from tsunamis. Comparison of resource use between two well-sampled houses before and after one tsunami suggests that while both households were resilient, they negotiated the event in different ways. Highlights: Reports on 1.2 million faunal remains from coastal village spanning 2150 years Overall consistency in animal use between pre-village and village occupation Changes in fish and invertebrate records consistent with tsunami impacts Social response to one tsunami differed between two households Overall community resilience shown in the face of multiple tsunamis